A Rapid Screening Method of Candidate Probiotics for Inflammatory Bowel Diseases and the Anti-inflammatory Effect of the Selected Strain Bacillus smithii XY1 - Huang, Xuedi; Ai, Fang; Ji, Chen; Tu, Pengcheng; Gao, Yufang; Wu, Yalan; Yan, Fujie; Yu, Ting (Frontiers in Microbiology, 2021)
Inflammatory bowel disease (IBD) is a chronic intestinal disease associated with the inflammatory gastrointestinal tract and microbiome dysbiosis. Probiotics are a promising intervention, and several probiotics have been reported to positively affect IBD remission and prevention, particularly on ulcerative colitis (UC). However, there’s still a limitation in the knowledge of effectiveness and safety of probiotics therapies for IBD. Exploring more potential probiotics helps to find extensive evidence for probiotic intervention. This study established a rapid method for probiotics candidate screening and finally screened out one strain with the best protective effect. Forty strains isolated from 4 different sources were used for this screening.Hemolysis tests and acute toxic test evaluated strain safety. Zebrafish were first treated with dextran sodium sulfate (DSS) for colitis induction, and every bacteria was individually added to the fish water subsequently. Results showed 8 strains could lower the larvae mortality within 3 days under a 0.6% DSS concentration, including Lacticaseibacillus rhamnosus GG, Lacticaseibacillus rhamnosus NBRC3425, Bacillus smithii DSM4216, Bacillus smithii XY1, Bacillus coagulans NBRC12583, Bacillus coagulans XY2, Lactobacillus parafarraginis XYRR2 and Bacillus licheniformis XYT3. Among 8, Bacillus smithii XY1 was the only strain having the equal ability to alleviate neutrophil infiltration in the larvae intestine with that ability of prednisolone under a 0.5% DSS concentration. Bacillus smithii XY1 restored intestinal epithelial cell integrity after DSS damage, as well as regulated the gene expression inflammation-related factors, indicating its bio-function of inflammatory response alleviation.